The Influence of Organizational Culture, Principal Leadership and Work Motivation to Teacher Commitment at SMPN Kepulauan Riau - Milasari; Risnita; Musli (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Abstract In schools, up to now there are still symptoms of problems related to organizational culture, principal leadership and work motivation with teacher commitment, so that in the aspect of teacher hard work it is still in the sufficient category and needs improvement. It is necessary to examine the influence of organizational culture, principal leadership and work motivation on teacher commitment. This research aims to examine the direct and indirect influence of organizational culture, principal leadership, and work motivation to teacher commitment at SMPN Kepulauan Riau. This research is research with an associative quantitative approach with a survey design taking the location of SMPN Kepulauan Riau. The population in this study was 801 teachers with civil servant status and the sample was 80 teachers. The results of the analysis show that there is a simultaneous direct influence between organizational culture, principal leadership and work motivation to teacher commitment at SMPN Kepulauan Riau with a multiple correlation coefficient of (0.460) with a contribution of (73.96%). The conclusion is that organizational culture, principal leadership and teacher work motivation partially or simultaneously influence teacher commitment. The implication is that the better the organizational culture, principal leadership and work motivation, the higher the teacher commitment at SMPN Kepulauan Riau.